The effect of CO2 emissions and economic performance on hydrogen-based renewable production in 35 European Countries. (12th November 2019) - Xu, Ran; Chou, Li-Chen; Zhang, Wan-Hao
Abstract: This study applies the OLS and panel data approach to estimate the influence of variables such as greenhouse gas emissions, per capita income, the scale of labor force input, the portion of added value in manufacturing industry and government mechanism on hydrogen-based renewable production in 35 European countries. The empirical results show that the nation's economic input and its income level have a positive effect on hydrogen-based renewable energy, which indicated that the economic growth has promoted living standards, inspired environmental awareness, and influenced the use of alternative energy and renewable energy. Moreover, the empirical results also show that deepening democracy (government mechanism) has a positive impact on hydrogen-based renewable energy in OECD countries, but the impact on non-OECD countries is not clear. Highlights: Analyzes the relationship between the emissions, economic on hydrogen-based renewable. Renewable production and economic indicators from 35 countries are studied. Nation's economic level has a positive effect on hydrogen-based renewable energy.